HUBUNGAN FUNGSI KELUARGA DENGAN PEMENUHAN AKTIVITAS PASCA STROKE LANSIA - Kusumaningrum, Umi Azizah (Jurnal EDUNursing, 2023)
Stroke occurs when blood vessels fail to supply oxygen and nutrients to brain cells. Elderly people with stroke will experience motor dysfunction and have physical limitations in performing self-care and meeting their daily needs. Therefore, the elderly will need a lot of help from caregivers or family in carrying out daily activities. The care provided to the elderly aims to help the elderly to be independent in carrying out daily activities. The purpose of this study was to determine the relationship between family function and the fulfillment of post-stroke elderly activities in Jabon Village, Mojoanyar District, Mojokerto Regency. This research design uses cross-sectional. The number of research samples was 33 respondents. The results showed that of the 5 respondents with good family function, most had a mild level of dependence, namely 3 respondents (60%), and of the 5 respondents with poor family function, almost half had a moderate and severe level of dependence as many as 2 respondents (40%). The results of the analysis using Spearman Rho show that the p-value significance value is 0.004 (<0.05) and the correlation coefficient value is (0.475) which can be concluded that the relationship is positive (unidirectional) which means that the better the family function, the lighter the level of independence of the elderly. The importance of increasing the function and role of the family to reduce the level of dependence on the fulfillment of post-stroke elderly activities. Keywords: Family function, Elderly activities, Stroke